Melatonin increases superoxide dismutase 2 (SOD2) levels and improves rat ovarian graft function after transplantation - Karla Krislane Alves Costa Monteiro; Luciana Lamarão Damous; Marcos Eiji Shiroma; Lara Termini; José Cipolla-Neto; Ricardo dos Santos Simões; Rinaldo Florencio da Silva; José Antonio Turri; Edmund C. Baracat; Jose Maria Soares-Junior (BMC, 2024)
Abstract Background Ovarian cryopreservation is a promising technique despite being hindered by damage from freezing and thawing. Melatonin can mitigate this outcome. Objective This study aimed to evaluate the effect of melatonin on the follicular dynamics of ovarian tissue in a cryopreserved cell culture. Methods Three-month-old adult female Wistar rats (n = 24) weighing approximately 250 g were oophorectomized and divided into two groups (n = 12): the control group (CG) and the melatonin group (MG). In the CG, slow cryopreservation was performed according to the standard protocol with Medium M2 and dimethyl sulfoxide (DMSO). In MG, melatonin diluted in ethyl alcohol vehicle at a concentration of 0.1 μm was added to the culture medium. In both groups, the ovaries were cryopreserved by slow freezing and kept in liquid nitrogen for 24 h. Subsequently, after thawing, the ovaries were reimplanted in the retroperitoneum, one on each side of the great vessels (inferior vena cava and aorta). After 30 days, the animals were euthanized during the diestrus phase; then, the grafts were removed and processed for histomorphometric and immunohistochemical analyses, whereas the blood was subjected to biochemical analysis. Student's t test was used to assess the difference between the groups. Results The FSH levels in MG (83.79 ± 32.37) were lower than those in CG (120.52 ± 36.59), p = 0.03. The FSH/AMH ratios were also lower in MG (3.53 ± 1.13) than in CG (6.52 ± 2.85), p = 0.001. The SOD2 immunoexpression was higher in MG than in CG regarding all parameters except for the degenerated follicles (follicular cells and internal thecal cells): CG (16.80 ± 4.80 [13.36-20.24]) and MG (14.91 ± 4.04 [12.01-17.79]) p = 0.351. Statistically, the difference in intact follicles (theca + interstitium) between CG (6.60 ± 2.59 [4.75-8.45]) and MG (9.31 ± 3.09 [7.09-11.51]) was significant (p = 0.049), with a small difference in the expression of regular antral follicles. Conclusions Melatonin can improve the quality of cryopreserved tissues, as evidenced in this study, and the evaluation of cryopreserved ovarian grafts, as shown in the melatonin group with better hormonal parameters and greater immunohistochemical expression of the SOD2 antioxidant. Thus, damage is reduced during cryopreservation and transplantation is improved.